Saudi Arabia's Position About the Iranian Islamic Revolution In 1979 - Othman, Nazem Y.; Shafiq, Nizar Z. (Humanities Journal of University of Zakho, 2018)
Saudi Arabia has occupied a prominent place regionally and internationally since it is characterized by religious، political and economic power. Saudi Arabia has paid serious attention to regional issues in general and to Iran in particular، especially during the internal events in Iran in 1978 and the Iranian revolution in 1979. The Saudi – Iranian relations have gained special importance in the formation of the Iranian relations with the Gulf countries due to the political، historical، religious and economic power of the two countries. The significance of the research is distinguished in shedding light on the Saudi position about the Iranian Islamic revolution in 1979. The research is divided into four parts، while the introduction of the research sets the ground for having a look at the Saudi - Iranian relations before 1979. The first part of the research highlights the position of Saudi Arabia about the internal events in Iran before the fall of the Shah. The second part is allocated for Saudi Arabia's position about the Iranian revolution. The third part investigates the position of Saudi Arabia about the principle of exporting the revolution abroad. The fourth part concentrated on the development of the relations between the two countries after the occupation of the American embassy in Tehran.